Impact of Users’ Education on Library Use Skills of Undergraduates in Selected Federal Universities in South-West Nigeria - Achugbue, Edwin I.; Adeyemi, Ojo; Adeyemi, Oluwabunmi Oluwaseun (Communicate: Journal of Library and Information Science, 2023)
The study examined the impact of users’ education on library use skills of undergraduates in selected federal universities in South-West, Nigeria. The study employed the survey type of the descriptive research design. The population of the study is 4126 undergraduates drawn from the registered 200 level undergraduate library users of the three (3) selected Federal Universities in South-West Nigeria. The sample size of the study is 351undergraduates, which constitute 8.5% of the entire population. The study adopted the simple random sampling technique. 351 copies of the questionnaire were administered, out of which 332 (95%) were returned and analysed using simple percentage, frequency count, mean and standard deviation. The findings of the study revealed that the types of library use skills instruction provided to the undergraduates among others are: bibliographic instruction, library orientation, library guide, guided library tour, a course on compulsory use of the library, library newsletter, library blog. Also, the study showed that to a high extent library use skills enhance the use of library resources by undergraduates.It was recommended that University management should support the librarian in the teaching of library use skill by equipping them with adequate facilities in theclassrooms and attaching unit to the course with compulsory nature of a pass in the grading system.